Revitalising the Juvenile Criminal Justice System in Indonesia: a Comparative Study with International Law and Evaluation of Practice - Yasmin Arinda Lubis; Reyva Cahyaningrum; Suci Andara Sari; Khashia Nadia Safitri (Journal of Ius Comparatum Law Studies, 2025)
Although it has been stipulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), the juvenile criminal justice system in Indonesia still faces challenges in ensuring the protection of children's rights. Therefore, this study aims to examine the urgency of revitalizing the juvenile justice system with a normative legal approach and empirical analysis. In this study, the author compares the juvenile justice system in Indonesia with international legal standards, and evaluates practices in courts to identify steps for improvement. The research findings indicate that the juvenile criminal justice system in Indonesia has not yet fully accommodated the principle of prioritizing optimal protection for children. Some of the problems found include violations of children's rights, social stigma, and lack of psychosocial support. In addition, limited facilities and professional staff at the Special Child Development Institution (LPKA) also hamper optimal rehabilitation of children. Thus, revitalizing the juvenile criminal justice system is urgent by optimizing diversion mechanisms, implementing restorative justice, increasing the capacity of law enforcement officers, strengthening the role of LPKA, and socializing to the community and families. With these efforts, the juvenile criminal justice system can be more responsive to developments in international law and there are concrete recommendations for policy makers to create a legal system that is more in line with the main priority of child welfare.